Relationship Between Residential Loction and Family's Asthma History with Night Cough in Children - Manggali, Agni Amurbatami (JURNAL KESEHATAN LINGKUNGAN, 2018)
Generally, children spend most of their time at home. In that way, the condition of their home will really affect their health. Children living in beside roadway may be exposed to emission of vehicles passing by the road and enter the house through the ventilation. Whereas, children are vulnerable of getting respiratory disease due to inhaling poluted air continously. The objective of this study is to analyze the relationship between living in house beside roadway and night cough in children. The sample of study was the students aged 6–7 years from SDN Babatan IV Surabaya and SDN Sumur Welut III Surabaya. Data collecting was done using cross-sectional method by filling out questionnaires interviewed to the parents of study sample. The questionaires used was International Study of Asthma and Allergy in Childhood (ISAAC) which had already translated to bahasa Indonesia and modified. Children who experienced night cough without flu was 26.15%. Children living in the roadside was 13.85%. Asthma history was had by 4.61% of children and 12.31% of their parents. Relationships were found between night cough and house in roadside (P = 0.045), asthma history of children (P = 0.016), and asthma history of parents (P = 0.003). This study conclude that distance between house and roadway is a significant modifier for night cough without flu in children. Recommendations that can be given through this study are conducting allergy examination for children and adding facilities to absorb air pollutants in houses located beside roadway such as indoor plants or screen for ventilation.